Pharmacology of Antisense Drugs - Bennett, C Frank; Baker, Brenda F; Pham, Nguyen; Swayze, Eric; Geary, Richard S (Annual review of pharmacology and toxicology, 2017)
Recent studies have led to a greater appreciation of the diverse roles RNAs play in maintaining normal cellular function and how they contribute to disease pathology, broadening the number of potential therapeutic targets. Antisense oligonucleotides are the most direct means to target RNA in a selective manner and have become an established platform technology for drug discovery. There are multiple molecular mechanisms by which antisense oligonucleotides can be used to modulate RNAs in cells, including promoting the degradation of the targeted RNA or modulating RNA function without degradation. Antisense drugs utilizing various antisense mechanisms are demonstrating therapeutic potential for the treatment of a broad variety of diseases. This review focuses on some of the advances that have taken place in translating antisense technology from the bench to the clinic.